Volutaria tubuliflora (Murb.) Sennen (Asteraceae), nueva especie alóctona asilvestrada para Chile - TEILLIER, SEBASTIÁN; MACAYA, JORGE; SUSANNA, ALFONSO; CALLEJA, JUAN ANTONIO (Gayana Botánica, 2014)
Volutaria tubuliflora (Asteraceae-Carduae) is described as a new alien plant species in Chilean vascular flora. The species has the widest range of natural geographical distribution of the genus being present from southern Europe to Arabic peninsula, inclusive Macaronesia. In Chile it has been naturalized in the Desert ecoregion, and it growths in the Atacama Region (III). Plants were found at Panamericana highway border, and apparently still have not invaded outside. In this paper we provide morphological and ecological information for this species.